Автоматизована система утилізації відходів - Подворний, В. Т. (ХНУРЕ, 2023)
This work is devoted to evaluating the effectiveness of an automated system for the disposal of household waste, namely: the system opened the lid when a hand approached. The work is considered to be the main design of automated household waste disposal systems. The system was verified by parametric analysis. Experiments were carried out to introduce a system of plastic containers. Based on the results of the analysis of the entire system, a system based on Arduino Nano proposed a functionality for automatically opening the lid when a hand approaches.